Analisis Pengaruh Komitmen Organisasi terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi di Kantor Bea Cukai Kota Surakarta - Ramadan, Ariel Rain Yusuf (Prosiding University Research Colloquium, 2022)
This study aims to analyze the effect of organizational commitment on employee performance with job satisfaction as a mediating variable. The population and sample in this study were employees of the Surakarta city customs office and the number of respondents as samples in this study were 100 people, but 80 people included in the research criteria. Sources of data used in this study is primary data. data collection method using a questionnaire. data analysis used using Smart PLS. (1) The results of the affective commitment variable have a positive and significant effect on job satisfaction. (2) The results of the continuance commitment variable have a negative but significant effect on job satisfaction. (3) The results of the normative commitment variable have a positive and significant effect on job satisfaction. (4) The results of the affective commitment variable have a positive but not significant effect on employee performance on employees. (5) The results of the continuance commitment variable have a positive but not significant effect on employee performance. (6) The results of the normative commitment variable have a negative and insignificant effect on employee performance. (7) The results of the job satisfaction variable have a positive and significant effect on employee performance on employees.